Gender relations and access to domestic rural water services in Manyoni District, Tanzania - Mfinanga, Fredrick Alleni; Masanyiwa, Zacharia Samwel; Mafwolo, Gemma; Erick, Stephen Bishibura (Publisher of Widyagama University of Malang (UWG Press), 2024)
The study examined the household division of labour, and household power relations in access to domestic water services in rural areas. This study was conducted in Manyoni District in Tanzania, used a cross-sectional research design whereby primary and secondary data were collected using questionnaire from 191 households randomly selected from two wards. In addition, Focus Group Discussion (FGD) method was used to collect qualitative data. Quantitative data were analyzed for descriptive statistics such as frequency and percentages and inferential statistics the chi-square test. Qualitative data were analyzed by using content analysis. The findings show that due to the traditional gender division of labor at the household level, women were the major seekers of domestic water for their households although some indications of equity in the household division of labor were also reported between boys and girls. Furthermore, most of the non-monetary decisions on access to domestic water were assigned to women whereas men were involved in the monetary decisions like paying user fees. It was concluded that gender relations played a role in access to domestic water services in the study area. It was recommended that the government should provide more improved water sources in rural areas to ensure access to many households, hence, reducing women’s burden of fetching water from distant sources and improving the welfare of women in rural areas.JEL Classification I26; J16; Q25To cite this article: Mfinanga, F. A., Masanyiwa, Z. S., Mafwolo, G., & Erick, S. B. (2024). Gender relations and access to domestic rural water services in Manyoni District, Tanzania. Journal of Socioeconomics and Development, 7(1), 104-114. https://doi.org/10.31328/jsed.v7i1.5516